Study on the durability of film adhesively bonded composite joints subjected to environmental aging - Alkoc, Ahmetcan; Yoruc, Afife Binnaz Hazar; Bakir, Mete; Usak, Adem Can (SAGE PUBLICATIONS LTD, 2026)
The research aims to illustrate the effectiveness of Atmospheric Pressure Plasma Treatment (APLT) activation in enhancing durability in achieving high performance for Carbon Fiber Reinforced Polymer (CFRP) adhesively bonded joints. The study addresses several crucial aspects, encompassing the surface characterization of different treated CFRP surfaces and durability Wedge Test performance assessments under severe environmental conditions for 576h. To attain this objective, the parameters of APLT were examined alongside chemical isopropanol cleaning and peel-ply methods, considering chemical surface characteristics, as well as the performance of joints under environmental conditions. Observations have indicated that APLT facilitates the formation of polar functional groups with increased oxygen content, improving wettability, and leading to substantial enhancements in durability. Finally, findings from the Wedge Test revealed that APLT demonstrates remarkable endurance under elevated temperature/wet aging conditions. It displayed superior resistance to crack formation and limited propagation, thereby preserving higher fracture toughness energy.
Keywords: Prepreg; fracture toughness; surface analysis; surface treatments; durability; ATMOSPHERIC-PRESSURE PLASMA; SURFACE-TREATMENT; PEEL PLY; FUNCTIONALIZATION; MORPHOLOGY; CHEMISTRY; STRENGTH; BEHAVIOR; ENHANCE; DESIGN; Materials Science; Polymer Science